Analysis of the Existence of Environmental Kuznets Curve: Evidence from India - Gopakumar, Goapl; Jaiswal, Ritika; Parashar, Mayank (International Journal of Energy Economics and Policy, 2022)
The study aims to estimate the Environmental Kuznets Curve (EKC) in the Indian context for the period of 1991-2018 by considering the role of economic growth, renewable energy, foreign direct investment, stock market size, energy intensity, and private investment in the energy sector with the help of autoregressive distributed lag (ARDL) cointegration technique. The results confirm the existence of an inverted U-shaped EKC relationship between economic growth and CO2 emission level. However, the estimation of turnaround point shows that CO2 levels have kept increasing past the turnaround point, indicating that income disparity is a decisive factor in determining emissions and is a better indicator than national income. Furthermore, results confirm the negative impact of economic growth and stock market size on the environment. In contrast, renewable energy, foreign direct investment, and energy intensity positively impact the environment in the long run. However, the impact of private investment is insignificant. Though the Indian economy continued to grow during the last few decades, the minimal investment towards renewable energy may not help to reduce the environmental problems. Hence, the nation’s income growth alone does not solve the ecological issues in the long run. In addition, it requires an increase in private investment towards the development of India’s renewable energy sector.